THE EFFECT OF BRAND IMAGE, BRAND TRUST AND CUSTOMER SATISFACTION ON REPURCHASE INTENTION (CASE STUDY: STARBUCKS COFFEE JAKARTA) - Br Tarigan, Anggi Pertiwi; Bernarto, Innocentius (JURNAL ILMIAH EDUNOMIKA, 2024)
This study set out to examine the beneficial effects of customer satisfaction, brand trust, and good brand. image on repurchase intention. The survey approach that was employed to examine the study's findings. A questionnaire instrument was used to carry out the data collection technique. The sampling technique used was purposive sampling. The target population of the study is all buyers of Starbucks Coffee products who have made at least two purchases. The sample size was determined as many as 250 samples. The data analysis technique uses the Partial Least Square-Structural Equation Modeling (PLS-SEM) approach from the SmartPLS program. The results showed that brand image and brand trust have a positive influence on customer satisfaction. Furthermore, brand image and brand trust have a positive influence on repurchase intention. Finally, customer satisfaction has a positive influence on repurchase intention.